Numerical experiments with a continuous L_2-exponential merit function for semi-infinite programming - Pereira, Ana I. P. N. (2008)
Here, we present some numerical experiments with a reduction method for solving nonlinear semi-infinite programming (SIP) problems. The method relies on a line search technique to ensure a sufficient decrease of a L_2-exponential merit function. The proposed merit function is continuous for SIP and improves the algorithm efficiency when compared with other previously tested merit functions. A comparison with other reduction methods is also included.